2011
DOI: 10.1103/physreva.84.052511
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Doppler-free electromagnetically induced transparency in atoms selected optically with specific velocity

Abstract: We observed an electromagnetically induced transparency signal in a four-level system with optically selected rubidium atoms at specific velocities in a room-temperature vaporized cell. Since the atoms behave like cold atoms in the selected atomic view, the observed signals coincide with a trapped atomic system. According to this result, we can observe Doppler-free signals, which correspond from 1.2 to 1.0 K in a Doppler-broadened medium. And the selected atoms have velocity components of ±(131 ± 3) MHz per wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moving the crossover peak position away enhances the signal sensitivity [17]. It is also worthy to note that VSPS gives us a signal similar to a cold atom [21].…”
Section: Nakayama Theory For Velocity Selective Birefringence Modelmentioning
confidence: 93%
“…Moving the crossover peak position away enhances the signal sensitivity [17]. It is also worthy to note that VSPS gives us a signal similar to a cold atom [21].…”
Section: Nakayama Theory For Velocity Selective Birefringence Modelmentioning
confidence: 93%
“…By analyzing the formation of crossover peaks, it is found that they can be used to select atoms with different velocities. [26][27][28] Taking the three-level system shown in Fig. 1(b) as an example, the group of atoms with velocity V = ±c(ν 1 − ν 2 )/(ν 1 + ν 2 ) in the direction of the incident laser beam can resonate with both the pump beam and the probe beam at the frequency…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The main advantages of using the five-level Λ−Ξ scheme are as follows. Firstly, it gives rise to multiwindow EIT that has potential applications like the optical nanofiber for guiding entangled beams [42], the influence of an external magnetic field [43] and velocity selection [44,45]. Secondly, under the condition of subluminal light propagation, enhanced Kerr nonlinearity with reduced absorption can be obtained near the line center for both the stationary and moving atom case.…”
Section: Introductionmentioning
confidence: 99%